Grünwald Implicit Solution of One-Dimensional Time-Fractional Parabolic Equations Using HSKSOR Iteration(Conference Paper) - Muhiddin, F.A.; Jumat Bin Sulaiman; Sunarto, A. (Institute of Physics Publishing, 2020)
This paper presents the application of a half-sweep iteration concept to the Grünwald implicit difference schemes with the Kaudd Successive Over-Relaxation (KSOR) iterative method in solving one-dimensional linear time-fractional parabolic equations. The formulation and implementation of the proposed methods are discussed. In order to validate the performance of HSKSOR, comparisons are made with another two iterative methods, full-sweep KSOR (FSKSOR) and Gauss-Seidel (FSGS) iterative methods. Based on the numerical results of three tested examples, it shows that the HSKSOR is superior compared to FSKSOR and FSGS iterative methods. © Published under licence by IOP Publishing Ltd.